Photodynamic therapy for early cancer of hollow organs - E. V. Filonenko; V. V. Sokolov; V. D. Menenkov; G. P. Krylova (Biomedical Photonics)
New medical technology of photodynamic therapy for cancer of hollow organs with photosens determines parameters of irradiation (sites of placement and position of light guide, number of positions and duration of irradiation) to reduce probability of injury during irradiation of intact mucosa in hollow organ due to optimization of light dose. The technology allows to avoid inflammatory and necrotic injury of intact mucosa on the contralateral wall of organ and late complications and to achieve complete tumor regression depending on localization in 73–87% of cases for follow-up period from 1 to 11 years.